Efficacy of Bilberry and Grape Seed Extract Supplement Interventions to Improve Glucose and Cholesterol Metabolism and Blood Pressure in Different Populations—A Systematic Review of the Literature - Grohmann, Teresa; Litts, Caroline; Horgan, Graham; Zhang, Xuguang; Hoggard, Nigel; Russell, Wendy; de Roos, Baukje (Nutrients, 2021)
Intervention with fruit extracts may lower glucose and lipid levels, as well as blood pressure. We reviewed the efficacy of bilberry and grape seed extracts to affect these outcomes across populations with varying health status, age and ethnicity, across intervention doses and durations, in 24 intervention studies with bilberry and blackcurrant (n = 4) and grape seed extract (n = 20). Bilberry and blackcurrant extract lowered average levels of glycated hemoglobin (HbA1c), at least in Chinese subjects, especially in those who were older, who were diagnosed with Type 2 Diabetes Mellitus (T2DM) and who were participating in longer-term studies. We also found good evidence that across studies and in subjects with hypercholesterolemia, T2DM or metabolic syndrome, intervention with bilberry and blackcurrant extract, and to some extent grape seed extract, significantly lowered total and low density lipoprotein (LDL) cholesterol levels after four weeks. Intervention with grape seed extract may reduce systolic and diastolic blood pressure in subjects with hypertension or metabolic syndrome. Differential responsiveness in cholesterol and blood pressure outcomes between stratified populations could not be explained by age, dose or study duration. In conclusion, bilberry and blackcurrant extract appears effective in lowering HbA1c and total and LDL cholesterol, whereas grape seed extract may lower total and LDL cholesterol, and blood pressure, in specific population groups.